Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Prestasi Dan Keaktifan Belajar Peserta Didik Pada Mata Pelajaran Komputer Dan Jaringan Dasar Kelas X Tkj 1 Smk Negeri 1 Kemusu Boyolali - sukamto sukamto sukamto; Afis Pratama; Handini Arga Damar Rani (Universitas Ivet, 2020)
The purpose of this study is 1) Increase the learning activities of Computer and Basic Network of Class X TKJ 1 students of SMK Negeri 1 Kemusu Boyolali to be better, 2) Increase and encourage the activeness of students in Computer and Basic Network subjects in Class X TKJ 1 of SMK Negeri 1 Boyolali Kemusu, 3) Knowing an increase in learning outcomes in Computer and Basic Networking Class X TKJ 1 students of SMK Negeri 1 Boyolali. Classroom Action Research (CAR) using 2 cycles, each cycle consisting of 3 meetings starting from the stages of planning, implementation, observation, and reflection. The subjects of this study were students of class X TKJ 1 SMK Negeri 1 Kemusu Boyolali in March 2019 to June 2019 with the number of students 25 (twenty-five). Data obtained by documentation, observation, and theory tests. Data analysis used descriptive percentage analysis. The results showed that (a) completeness of student learning from the initial or pre-cycle conditions with test results of only 28% or 7 students from 25 students increased to 48% or 12 students from 25 students in the first cycle, an increase of 20% or 5 children, and increased to the results of the second cycle test by 80% or 20 students out of 25 students, which showed an increase of 32% or 8 children. (b) The activeness of students who fall into the